Utilization of Learning Videos as Media to Improve Students' Conceptual Understanding in Islamic Education Learning at SD Negeri No.104293 Makmur - Yanthy, Julya Dharma; Sumarno (Jurnal Profesi Guru Indonesia, 2024)
This study aims to determine the effectiveness of the use of Islamic educational videos in improving students' understanding of prayer procedures in grade V of Elementary School. The background of this study is based on the problem of low levels of students' understanding of the sequence of movements and readings in prayer. This is generally caused by learning methods that are still conventional, namely the dominance of lectures and the lack of attractive visual learning media. In this study, the researcher used a descriptive qualitative approach, with data collection techniques that included observation of the learning process, interviews with teachers and students, and evaluation tests to measure improvements in student understanding. The subjects of the study were grade V students at a State Elementary School. The results of the study showed that the use of Islamic educational videos had a positive impact on students' understanding. Videos that clearly visualize prayer movements and readings can help students understand the material more deeply. Students also showed a higher interest in learning because the learning media used were more interesting and interactive than conventional methods. Thus, it can be concluded that Islamic educational videos are effective learning media and can be a very good alternative to improve the quality of Islamic Religious Education learning, especially in the material on prayer procedures at the elementary school level.